A magnetic metal–organic framework as a highly active heterogeneous catalyst for one-pot synthesis of 2-substituted alkyl and aryl(indolyl)kojic acid derivatives. (26th June 2017) - Zhang, Hong-Yan; Hao, Xiao-Peng; Mo, Li-Ping; Liu, Sha-Sha; Zhang, Wen-Bo; Zhang, Zhan-Hui
Abstract : A novel magnetic metal–organic framework, NiFe2 O4 @MOF-5, was prepared and demonstrated to be a highly efficient catalyst for the one-pot three-component reaction of aldehyde, indole, and kojic acid. Abstract : A novel magnetic metal–organic framework, NiFe2 O4 @MOF-5, has been prepared and characterized using spectroscopic, microscopic, and magnetic techniques (FT-IR, XRD, TEM, SEM, EDX, and VSM). This magnetically separable catalyst exhibited high catalytic activity for the synthesis of a variety of 2-substituted alkyl and aryl(indolyl)kojic acid derivatives via a one-pot, three-component reaction of aldehyde, indole, and kojic acid under solvent-free conditions. The catalyst can be easily magnetically separated and exhibits significant recyclability, with no significant loss of activity after six consecutive runs.